A strategic management term paper for Bulacan Sweets and Delicacies Center: A paper - Veneracion, Ma. Caroline L. (Animo Repository, 2003)
The Food Processing Industry: Today, the food processing industry is very broad that includes a wide array of edible and potable: fruits and vegetables, fish, milk, meat and poultry, grains, etc. Packaged and convenience foods as well as beverages are also considered processed foods. Food and beverage processing is the main manufacturing activity in the Philippines. This industry alone accounted for almost 40 percent of the total manufacturing sector's gross value-added during 2000. It also managed to raise the sector's performance amidst the economic slowdown, growing by approximately five percent from the same period in the previous year, while other manufacturing industries either remained stagnant or experienced negative growth. There are 4,914 food processing companies in the country, about 30 percent (1,455 companies) of which are located in Metro Manila. Most of the companies are owned by a single proprietor, which are common among micro, cottage and small industries, and corporations which are confined to large-scale processors. A study revealed that among small and medium enterprises, the food processing industry generated the most jobs contributing 25 percent of employment created. The local market is the predominant outlet of products produced by processors, while nearly one fourth of the respondents belonging to the medium and large-scale processors export their products. Dramatic changes are occurring in the way in the way retail establishments deliver food to the consumers, mainly in response to dynamic and diverse trends in lifestyles. Fundamental changes in demographics, labor force participation, and income distribution continue to dictate changes in the food system. The most successful firms are organized to develop and deliver the best combination of food and service to consumers. Basic production, processing, logistics and marketing strategies in companies are focused on producing goods and services that will bring back customers. Porter's Five Competitive Forces: (1) Rivalry Among Competing Firms (2) Buyers (3) Suppliers (4) Substitute Products (5) Potential New Entrants Threats and Opportunities in the Industry: Threats: (1) Changing consumer tastes and lifestyles (2) Globalization (3) Peace and Order Situation Opportunities: (1) E-commerce (2) Technology and Development The Company - Bulacan Sweets and Delicacies Center: Bulacan Sweets and Delicacies Center was established in the early 70's by Mrs. Lydia Veneracion, a housewife who hailed from the town of San Miguel in Bulacan. Her first store was located at the corner of Labo St. and N.S. Amoranto Ave. in Laloma, Quezon City. The company is engaged in the distribution of native Filipino sweets and delicacies coming from the different parts of the country. Their products are very popular among balikbayans who buy their products as gifts or pasalubong to their families when they go out of the country. The company later added canning services to customers where delicacies like lechon paksiw, bagoong, binagoongan and taba ng talangka, are canned. At present, Bulacan Sweets has seven outlets. These are located at SM North Edsa, SM Megamall, SM Southmall, 1st and 3rd Level of Landmark, Tropical Hut Hamburger in Quezon Ave., and Park and Ride in Manila City Hall. From the time the business was established, no formal organizational structure was put into place and the business was run on an informal basis. In 1991, Loly Veneracion, one of the daughters of Mrs. Lydia Veneracion, took over and organized the operations. Bulacan Sweets, despite its current size, does not have a formal vision statement nor do they have any clear-cut goals in the long-range. Being a family endeavor, its plan and strategies are often conceived around the dinner table. The following are the proposed corporate objectives: (1) To penetrate a new market in the United States in 3 years (2) To streamline operations to make the company profitable in 1 year by reducing costs in inventory (3) To formalize the different functional areas in the company by developing written and formal guidelines in each area in 2 years. Present Strengths and Weaknesses Strengths: (1) The company is the pioneer in the retailing of native delicacies and has already established its brand name since it is the first to offer original Filipino products (2) The company's name is not only known to local customers but as well as to balikbayans (3) The company offers a unique service, canning, not offered by competitors (4) Morale is high since the company treats their employees as part of their family. Weaknesses: (1) The facilities and methods used to sell to customers have been the same since the company started (2) Product line breadth and depth are too diverse that cause of their products to compete with each other (3) Based on the Financial Ratio Analysis, the company has been incurring loss for the past two years (4) The company does not have ready access to outside/new funds but depended mainly on the business of one of the children of the owner (5) The company has no formal and written policies and procedures on personnel management (i.e., hiring, performance appraisal, training and reward) (6) The company uses a manual system in their inventory management which is often tedious and prone to pilferages (7) The company does not have succession management to address the complexities involved for the founder and the family in making transitions that are essential for the ongoing vitality of the business. The founder is already in her late 60's. Present Strategies of the Company Bulacan Sweets does not have defined strategies they use in sustaining the business. Basically, if profits are up they look for a location where they can put up a new outlet. However, there were also instances when outlets were closed down whenever sales on these outlets were low or there was a need for additional funds for the operations of the business. Most of their products come from over 40 suppliers. Some products are on consignment basis and the rest are already considered as sold from the suppliers. Not all products they carry become permanent on their product lines. There are products that they usually test for viability for a few months. If there is sustained demand for these products, this is the only time they included them permanently in their product lines. The company has been operating for over three decades. The management style has not undergone any dramatic change over the years. They consider their candied fruits as one of their most essential products. The company capitalized on the exotic tropical fruits found in the country. Since dried fruits are becoming popular now because the public's growing concern with health, the company has considered exporting their products. Proposed Corporate Strategies: (1) Export Candied Fruits in th U.S. (2) Optimize Width of product Line (3) Implement Total Quality Management (TQM). Proposed Functional Strategies: (1) Marketing (2) Finance (3) Operations. Human Resource Development Professionalizing the personnel management of Bulacan Sweets will include the following: (1) Writing job descriptions (2) Developing and implementing an employee performance appraisal system (3) Improving attendance/disciplinary procedures and documentation (4) Providing employee training (5) Succession management. Information Management The following are possible IT configurations that the company can use: (1) Use of a database management system to help in the monitoring of their inventory (2) Use of POS software to facilitate an efficient product code encoding for each sales transaction. Today, the use of computer systems to control inventory is far more feasible for small business than ever before, both through the widespread existence of computer service organizations and the decreasing cost of small sized computers. Often the justification for such a computer-based system is enhanced by the fact that company accounting and billing procedures can also be handled on the computer. Competitive Advantages The following are the company's competitive advantages: (1) More variety of products (2) More outlets/branches (3) More brand popularity (4) Pioneer in the business (5) Premium quality of products. Company's Capability to Implement Strategies The company's structure is informal and centralized. The owner with consultation with the member of the family makes the major decisions. There are no formal and written guidelines for the different functional areas of the company. The company hires consultants when the need arises. The operations are highly manual (i.e., inventory management). There are no written guidelines on the hiring practices of the company. The training given to new employees is informal and basic consisting mainly of customer service and product proficiency. Eventually, employees acquire the skills on good customer service by emulating the owner, known for being very charismatic to customers. The owner and members of the family are very informal with their treatment to their employees. Employees are treated as family members and they can easily approach and talk to the owner and her family. This has inspired them to be loyal to the company and have a sense of pride on the products and services the company provides. Tasks to be Performed to Make Company Capable of Implementing Strategies There are a lot of tasks to be performed to make the company capable of implementing the proposed strategies. The challenge lies on creating a strong business structure that will support the strategy implementation. The resources needed to make the capable include getting the right people who are motivated and skilled, being financially capable, creating strategy-supportive policies and building an environment and culture to fit the strategies."